Contributions to pegmatite exploration within granitic plutons in Central and Northern Portugal - Pereira, B. (2013)
Exploration programs for granitic pegmatites face the lack of detectable contrasts, either geophysical or geochemical, between pegmatites and their granitic host-rocks. The known productive sectors bearing pegmatites located inside granitic plutons, with economic interest for quartz and feldspar provide adequate field testing for alternative research, dealing with the peculiarities of lithological diversity and the arrangement of structural elements, around pegmatite swarms at suitable granite cupolas. The most efficient assessment for pegmatite positioning in tactical stages of exploration is the use of geological factors analyzed through raw or specifically treated remote imagery, enhancing the favorable lineaments and the most productive granite-host matrixes. The identification of targets using this approach led to a reasonable success tested by experimental drilling in some selected sites.